An insight into the influence of morphological and compositional heterogeneity of an individual intermetallic particle on aluminium alloy corrosion initiation. Issue 3 (4th May 2012) - Davoodi, A.; Pan, J.; Leygraf, C.; Parvizi, R.; Norgren, S.
Abstract In this work, a multi‐analytical in situ and ex situ approach was used to provide information needed to identify the role of an individual heterogeneous intermetallic particle (IMP) in localized corrosion initiation of aluminium alloys. The heterogeneity of the IMP was studied by combining atomic force microscopy (AFM), scanning electron microscopy and energy dispersive spectroscopy (SEM–EDS) and scanning electrochemical microscopy (SECM). A complex Al–Mn–Fe–Si IMP phase with different chemical composition in its inner and outer parts was characterized by SEM–EDS analysis. AFM results uniquely revealed a brain‐like feature of an IMP with 20 nm height variations. Submicron sized galvanic cell induced by morphological and compositional heterogeneity resulted in a localized corrosion attack inside the individual IMP. Various collected current levels measured by SECM were associated to the morphological and compositional heterogeneity of IMPs.